2016
DOI: 10.1038/nm.4041
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of DDR1 and Notch signaling is a therapeutic strategy for KRAS-driven lung adenocarcinoma

Abstract: Patients with advanced Kirsten rat sarcoma viral oncogene homolog (KRAS)-mutant lung adenocarcinoma are currently treated with standard chemotherapy because of a lack of efficacious targeted therapies. We reasoned that the identification of mediators of Kras signaling in early mouse lung hyperplasias might bypass the difficulties that are imposed by intratumor heterogeneity in advanced tumors, and that it might unveil relevant therapeutic targets. Transcriptional profiling of Kras(G12V)-driven mouse hyperplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 62 publications
7
146
0
Order By: Relevance
“…A recent study has shown that DDR1 was an interesting biomarker in renal cancer and that it promoted the epithelial to mesenchymal transition in cancer cells [27] . DDR1 expression was also enhanced in the early phases of KRAS-driven lung adenocarcinoma and its inhibition in vivo protected mice in an experimental model of this disease [28] . However, the molecular mechanisms downstream DDR1 activation in cancer cells are mostly unknown.…”
Section: Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has shown that DDR1 was an interesting biomarker in renal cancer and that it promoted the epithelial to mesenchymal transition in cancer cells [27] . DDR1 expression was also enhanced in the early phases of KRAS-driven lung adenocarcinoma and its inhibition in vivo protected mice in an experimental model of this disease [28] . However, the molecular mechanisms downstream DDR1 activation in cancer cells are mostly unknown.…”
Section: Cancermentioning
confidence: 99%
“…Recent investigations have reported the synthesis of specific DDR1 and/or DDR2 inhibitors tested in vitro and/ or in vivo [28,48,49] . Kim et al [48] created 2 specific inhibitors of DDRs, DDR1-IN-1, and DDR1-IN-2 derived, respectively, from nilotinib and imatinib.…”
Section: Ddr1 As Target Of Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In K-Ras-mutant lung cancers, Ambrogio et al (43) showed that combining 7rh to inhibit DDR1 with a Notch inhibitor was effective. In addition Ali-Rahmani et al (44) have shown inhibiting DDR1 with 7rh in combination with an immunotoxin caused shrinkage of tumor xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…DDR1 can induce pro- (5,44,69,71,72) and anti-(73-75) proliferative effects depending on the cell type. It was previously demonstrated that in KRAS-driven lung adenocarcinoma, DDR1 and Notch co-inhibition suppressed the activation of critical tumor survival-promoting signaling pathways (76). High DDR1 expression may also exhibit a positive effect in the proliferation and/or survival of breast cancer cells (46,77).…”
Section: Effects Of Ddr1 On the Apoptosis Or Survival Of Breast Cancementioning
confidence: 99%